Canva-Based Educational Game Media to Improve Fifth Grade Reading Skills: Media Permainan Pendidikan Berbasis Canva untuk Meningkatkan Keterampilan Membaca Siswa Kelas Lima - Hasmalia, Hasmalia; Munirah, Munirah; Adam, Andi (Indonesian Journal of Innovation Studies, 2025)
General Background: Improving reading comprehension among elementary students remains a significant educational goal, particularly in adapting learning methods to digital media. Specific Background: In rural or under-resourced settings like SD Negeri 78 Bakke, Soppeng Regency, integrating technology such as Canva can offer innovative pedagogical solutions. Knowledge Gap: While digital learning tools are widespread, studies on Canva-based educational games specifically targeting reading comprehension in younger learners are limited. Aims: This study aims to develop and evaluate a Canva-based educational game media for fifth-grade students to enhance reading comprehension skills through the Four-D (Define, Design, Develop, Disseminate) R&D model. Results: The resulting media achieved a validity score of 97% by expert judgment, a practicality score of 95.83% from implementation observations, and high response ratings from both teachers (91.66%) and students (96%). It was also deemed effective, as shown by improved scores from Trial I (35–65 to 75–95) and Trial II (35–80 to 75–100). Novelty: This research introduces a validated and gamified Canva-based media for reading, a novel approach in Indonesian elementary contexts. Implications: The findings suggest that integrating design-based educational games in classroom practice can effectively improve literacy outcomes and student engagement. Highlights: Enhances reading skills using Canva-based games. Proven valid, practical, and effective through trials. Innovative approach for engaging elementary learners. Keywords: Educational Games, Canva, Reading Comprehension, Elementary Students, Media Development